Spermiogenesis and spermatozoa ultrastructure in the Serrasalminae (Ostariophysi: Characiformes) with further evidence on the relationships of the piranhas and pacus - Gusmão-Pompiani, Priscila; Malabarba, Luiz R.; Oliveira, Claudio [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Sociedade Brasileira de Ictiologia, 2009)
A ultraestrutura dos espermatozoides e espermiogênese foram estudadas nas espécies Piaractus mesopotamicus, Mylossoma duriventre, Serrasalmus maculatus e Metynnis mola de Serrasalminae, sendo dois padrões distintos reconhecidos: um comum a Mylossoma, Serrasalmus e Metynnis, e o segundo característico de Piaractus. Este último é mais similar ao observado em Salminus e Brycon. Por outro lado, o espermatozoide dos serrasalmíneos compartilha algumas características com espécies da superfamília Anostomoidea. O significado filogenético destes caracteres é discutido.

Spermatozoa and spermiogenesis ultrastructure were studied in the serrasalmine species Piaractus mesopotamicus, Mylossoma duriventre, Serrasalmus maculatus, and Metynnis mola and two distinct patterns may be recognized: the first common to Mylossoma, Serrasalmus and Metynnis, and the other, characteristic of Piaractus. The latter pattern is more similar to the conditions found in Salminus and Brycon. on the other hand, serrasalmine spermatozoa also share characteristics with the spermatozoa of species of the superfamily Anostomoidea. The phylogenetic significance of these characters is discussed.
Keywords: Characid; Spermatid; Spermatozoa; Phylogeny; Morphology